A Forecast of the Future of American Railroads - Daniels, Winthrop M. (Quarterly Journal of Economics, 1924)
Introduction: the alarmist and the fatalist attitude; the problems to be solved, 364. — I. Transportation Technique; how recent its great advances, 365. — Motor-truck possibilities, 368. — Centralized generation of power, 371. — II. Terminals, 371. — Unitary control inevitable, 374. — III. Consolidations, 375. — Future of the Transportation Act in this regard uncertain, 376. — Public advantage of consolidation, 377. — IV. Ownership and Control, 378. — Financial difficulties arising from the legal limitation of return, 380. — Possible eventual outcome: a few great corporations, mixed directorates, 382.